Epidemiological and clinical characteristics of imported falciparum malaria in the Republic of North Macedonia : A 13-year experience - Bosilkovski, Mile; Khezzani, Bachir; Poposki, Kostadin; Semenakova-Cvetkovska, Vesna; Vidinic, Ivan; Lloga, Arlinda Osmani; Jakimovski, Dejan; Dimzova, Marija (Springer Science and Business Media LLC, 2023)
Plasmodium falciparum is the leading cause of imported malaria and the most common cause of death in returning travellers. Aim To identify the main epidemiological and clinical characteristics of patients with imported falciparum malaria in the Republic of North Macedonia. Material and methods Retrospectively analyzed were the epidemiological and clinical features of 34 patients with imported falciparum malaria who were diagnosed and treated at the university clinic for infectious diseases and febrile conditions in Skopje from 2010 to 2022. Malaria diagnosis was based on the microscopic detection of parasites in thick and thin blood smears. Results All patients were male, with a median age of 36 years and a range of 22–60 years. Of the patients 33 (97.1%) acquired the disease in Sub-Saharan Africa. All patients except one stayed in endemic regions for work/business purposes. Chemoprophylaxis was completely applied in 4 (11.8%) patients. The median time of onset between the symptoms and diagnosis was 4 days, with a range of 1–12 days. Prevailing clinical manifestations were fever, chills, and splenomegaly in 100%, 94%, and 68% of patients, respectively. Severe malaria was noticed in 8 (23.5%) patients. In 5 (14.7%) patients the initial parasitemia was higher than 5%. On admission, thrombocytopenia, hyperbilirubinemia, and elevated alanine aminotransferase were registered in 94%, 58%, and 62% of patients, respectively. Out of the 33 patients with adequate follow-up, the outcome was favorable in 31 (93.9%). Conclusion In every febrile traveller returned from Africa, imported falciparum malaria should be an essential part of differential diagnostic considerations.